Falso consenso: el fantasma de la buena fe en el artículo 7(1) de la CISG - Varsi-Rospigliosi, Enrique (2022)
Good faith is one the matters that divides Civil Law from Common Law systems and is a starting point to discuss on the underlying philosophy found behind the pro-good faith and anti-good faith approaches. Taking this context into consideration, the CISG adopted a restrictive model of good faith (Common Law-friendly, in principle) and so it was expressed in its text, being article 7(1) the only provision that makes reference to good faith and regarding the interpretation of the CISG. However, since it was a false consensus, the story did not end there, and the ghost of civilian good faith continues to haunt the CISG facilities, and thus, even if it is not physically present, its presence could be felt through the lex mercatoria pursuant to article 9 CISG.